Impact of localisation of deep brain stimulation electrodes on motor and neurobehavioural outcomes in Parkinson's disease. Issue 7 (21st August 2015) - de Chazeron, I; Pereira, B; Chereau-Boudet, I; Durif, F; Lemaire, J J; Brousse, G; Ulla, M; Derost, P; Debilly, B; Llorca, P M
Abstract : Background: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) represents a well-established treatment in advanced Parkinson's disease (PD) for motor signs, but it is still debated concerning psychiatric effects. Objective: Exploration of relation between position of active electrode contacts and neuropsychological and motor change after STN DBS procedure for PD. Methods: A cohort of 34 patients who underwent STN DBS was followed for 6 months. Preoperative and postoperative assessments included mood evaluation (depression and mania) and motor status. Active contact localisation was identified regarding position into the STN (4 groups: IN meant contacts were IN-IN IN-BORDER; OUT: OUT-OUT or OUT-BORDER; BORDER: BORDER-BORDER; IN-OUT: IN-OUT) and compared with clinical outcomes. Results: STN DBS significantly improved motor scores and reduced dopaminergic medication when compared with baseline and active lead groups: the best result was seen with the IN group. At 3 and 6 months postsurgery, depression and manic scores do not significantly differ compared with baseline and between leads groups. Focusing on symptom domains and compared with baseline, a significant loss of appetite was observed for the IN group at M3 and a significant increase in appetite from baseline was observed at M3 for the OUT group. Graphic representations illustrate that postsurgery evolution parameters at M3 or M6 are very good discriminant variables and well differentiate all leading groups. Conclusions: Stimulation of zona incerta may influence appetite and weight gain. Our clinical results seem to support a personalised DBS-targeted Parkinson therapy including individual motor and non-motor parameters.